Presence of a very virulent genotype of infectious bursal disease virus in vaccinated layer hens in Turkey - Ceribasi, Ali Osman; Bulut, Hakan; Gulacti, Irem; Eroksuz, Yesari; Bolat, Yusuf (Tubitak Scientific & Technological Research Council Turkey, 2007)
Despite vaccinations against very virulent (vv) strains of infectious bursal disease virus (IBDV) or Gumboro, Gumboro outbreaks in vaccinated hens in Turkey are still reported. These outbreaks suggested that new vv strains might have emerged and the present vaccines might not be able to provide protection against infections with these strains. The objective of this study was to characterize the viruses isolated from vaccinated layer hens. For this purpose, the hypervariable region of the VP2 gene of the viruses was amplified by reverse transcriptase- polymerase chain reaction (RT- PCR) and the amplification products were sequenced. These results showed that the field isolates of IBDV were more closely related to the European and Asian vv strain rather than the classical virulent strain, and the Gumboro outbreaks in Turkey were not derived from a new vv strain.
Keywords: IBDV; VP2 gene; sequence analysis